Phase space electron hole in the Venusian upper mantle boundary - Ahmed Gamal; Waleed Moslem Moslem; Mohamed Saleh Yousef; Ali Yahia Ellithi (Scientific Reports)
Abstract The fluctuations based on the “phase space electron hole” in the Venusian upper mantle boundary due to the Parker Solar Probe (PSP) and Pioneer Venus Orbiter (PVO) observations are detected. This study examines the characteristics of ion-acoustic solitary waves and double-layer structures. The influence of various plasma parameters on the wave properties is investigated to gain a better understanding of the formation and propagation of these non-linear structures. The Schamel-KdV equation is derived using a hydrodynamic description, accounting for a small percentage of non-isothermal trapped electrons. A parametric investigation was then conducted, utilizing spacecraft observations of the plasma configuration at Venus, including observed data of densities, temperatures, and velocities. Solitary waves and double-layer structures can exist in two different modes: slow and fast. In order to identify which structure is most closely matched with PVO observation for Doppler-shifted frequencies of $$\sim$$ 5.4 kHz and an electric field of $$\sim$$ 15 mV/m, we examined these structures in the context of available data. It is found that our results of the ion-acoustic wave in fast mode are in agreement with the mission data from PSP and PVO.